Realised safety impacts of electronic stability control in Finland. Issue 3 (24th March 2017) - Öörni, Risto; Luoma, Juha
Abstract : The objective of the study is to estimate the realised safety effects of electronic stability control (ESC) in Finland in the current context. The modelling of impacts was based on a framework in which the outcomes of accidents are determined by exposure of road users, accident risk and accident severity. Exposure to risk was modelled in three ways: (i) by calculating the share of passenger cars equipped with ESC with a mathematical model, (ii) on the basis of an ESC fleet penetration estimate obtained from a survey targeted to car importers and (iii) with ESC fleet penetration taking into account the penetration estimate obtained from the survey weighted with the annual kilometrage of passenger cars. The results of the study suggest that around 37 fatalities and 747 injuries were avoided in Finland in 2014 because of ESC.